Aplikasi Sistem Pendukung Keputusan Penilaian Kinerja Karyawan untuk Kenaikan Gaji pada PT AAA - Widyassari, Adhika Pramita (Universitas Nusantara PGRI Kediri, 2017)
PT AAA is a company engaged in the process of instrumentation and electrical design, procurement and construction of instruments. In an effort to improve employee performance PT AAA provide salary increase to employees who have good performance. In employee salary increases are sometimes not in accordance with the results of its performance. Employee salary increases are often hammered flat, or sometimes pay raise only by ingesting it, without the application of strong calculations. That is why there is an application of decision support system employee performance appraisal for a raise. One of the methods used is using Analitycal Hierarchy Process (AHP) method. This method is chosen because it is able to complete the assessment of employee performance based on predetermined criteria, which will be used as a reference in the raise of the salary itself. The results of the application of decision support system employee performance appraisal for salary increase not only determine who the employees are eligible to get a raise but also determine how much percentage of salary increase each employee.